Synthesis and Antioxidant Characteristics of Borate Esters Used in Lubricating Oil - Shekarriz, M.; Ghanbari, B.; Taghipoor, S.; Khalili, A.A.; Hajialiakbari, F.; Adibi, M.; Soleymani, M. (Asian Journal of Chemistry, 2010)
In the present studies, the preparation of esters of boric acid with hindered phenols is reported, wherein the alkyl groups are branched on the α-carbon atoms. The products were evaluated in terms of their oxidative stability. In most cases, improvements in oxidative stability in a hydrocarbon media (cumene) were observed.